1997
DOI: 10.1152/ajpendo.1997.273.2.e425
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of visceral adipose tissue and glucose disposal is independent of sex in black NIDDM subjects

Abstract: To determine the interrelationship among insulin action, total or regional adiposity, and sex, we measured insulin-mediated glucose disposal by the euglycemic insulin clamp and adipose distribution using computed axial tomography (22 scans) in 32 black men and 20 black women with non-insulin-dependent diabetes mellitus (age 48 +/- 9 and 54 +/- 9 yr, body mass index 26.3 +/- 2.3 and 27.2 +/- 2.6 kg/m2, respectively). Women had approximately 80% more total and subcutaneous fat volume than men (31.8 +/- 8.3 vs. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 25 publications
5
71
0
1
Order By: Relevance
“…The observation of mild insulin resistance, hyperinsulinaemia, elevated plasma TAG and LDL3, and lower HDL-C supports previous reports of migrant Indians presenting with characteristics of the metabolic syndrome. 1,13,15,17,18,38 Our report of comparable central adiposity in the two ethnic groups, although not consistently observed, has also been reported by others using indirect measures of central adiposity. 15,18 Body fat accumulation, especially that in the abdominal region, was positively associated with hyperinsulinaemia and all surrogate measures of insulin resistance and negatively associated with measures of insulin sensitivity in both the Caucasian and Sikh men.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observation of mild insulin resistance, hyperinsulinaemia, elevated plasma TAG and LDL3, and lower HDL-C supports previous reports of migrant Indians presenting with characteristics of the metabolic syndrome. 1,13,15,17,18,38 Our report of comparable central adiposity in the two ethnic groups, although not consistently observed, has also been reported by others using indirect measures of central adiposity. 15,18 Body fat accumulation, especially that in the abdominal region, was positively associated with hyperinsulinaemia and all surrogate measures of insulin resistance and negatively associated with measures of insulin sensitivity in both the Caucasian and Sikh men.…”
Section: Discussionsupporting
confidence: 83%
“…8,10 Therefore, it is unlikely that obesity per se is a viable explanation for the high prevalence of hyperinsulinaemia, although epidemiological data suggest that there may be a clearer association between central body fat, especially visceral fat, and insulin resistance, diabetes and CHD. 17 This relationship has been investigated by a small number of groups, but they have produced conflicting findings on the relationship between type II diabetes and a measure of central fat (waist:hip ratio). 8,10 Overall, the available data suggest that symptoms of the metabolic syndrome occur at a lower BMI in Indian Asians than in other population groups.…”
Section: Introductionmentioning
confidence: 99%
“…31 Asian Indians have relatively higher truncal and abdominal fat mass as compared to Caucasians and black population despite similar or less average value of waist circumference. 8 Banerji et al 32 showed that visceral adipose tissue mass of Asian Indians was identical to African- 33 Finally, truncal subcutaneous fat was significantly higher in Asian Indians having lower waist circumference than white Caucasians. 34 High body fat and truncal and abdominal adiposity may result in insulin resistance and other cardiovascular risk factors to manifest in Asian Indians at a lower value of waist circumference than white Caucasians.…”
Section: Discussionmentioning
confidence: 97%
“…44 Moreover, a recent report noted that olanzapine therapy in patients with first episode schizophrenia causes an increase in central body fat deposition that is associated with raised triglyceride and insulin levels. 45 Because this type of weight gain is often coupled with insulin resistance, 46 it is a significant long-term health issue. Taken together, these results suggest that drug choice may have a considerable impact on patient weight and health.…”
Section: Weight Gainmentioning
confidence: 99%